The biological and reproductive parameters of the invasive armored catfish Pterygoplichthys disjunctivus from Adolfo López Mateos El Infiernillo Reservoir, Michoacán-Guerrero, Mexico - Rebeca Aneli Rueda Jasso; Antonio Campos Mendoza; Francisco Arreguin Sánchez; Edmundo Díaz Pardo; Carlos Antonio Martínez Palacios (Revista Mexicana de Biodiversidad)
Invasive Pterygoplichthys disjunctivus (Weber, 1991) (synonymy: Liposarcus multiradiatus) armored catfish were first reported in Mexico in 1995 and have spread successfully in several aquatic ecosystems. In Adolfo López Mateos El Infiernillo Reservoir, Michoacán – Guerrero, the population of this armored catfish is growing substantially because natural predators are not present and exploitation by humans does not occur. Over a complete annual cycle, we studied the following population parameters: weight, total and standard length, the relationship of weight to total length, the hepatosomatic (HSI) and gonadosomatic (GSI) indices, total fecundity (TF) and relative fecundity (RF). The average total (TL) and standard lengths (SL) were 248 ± 37.5 and 188 ± 30.7 mm, respectively, and the average weight (W) was 135.3± 66.8 g. The largest fish reported was 520 mm in TL and weighed 1 280 g. The species showed an extended reproductive season from May to November, as indicated by the GSI, TF and RF. The strongest reproductive peak occurred from July through October. During the annual cycle, the highest monthly average fecundity was 2 447 eggs, and the average relative fecundity was 12.6 eggs per g of fish (August and September). This information will be crucial for calculating the current biomass and future growth of the population. The calculation of these results could provide a basis for the exploitation of this resource for human consumption and animal feeds.